Thyroid disorders and their role in the pathogenesis of glaucoma - T. V. Chernyakova; H. Y. Zargaryan; A. Yu. Brezhnev; O. N. Onufriychuk; I. R. Gazizova; А. V. Seleznev; А. V. Kuroyedov (Российский офтальмологический журнал)
The literature analysis confirms the interrelationship of thyroid gland pathology and glaucoma. Patients with diffusetoxic goiter (DTG) and endemic goiter have an especially high risk of developing glaucoma, while those with autoimmune thyroiditis face a moderate risk. The prevalence of primary open angle glaucoma (POAG) in patients over 40 with endocrine ophthalmopathy is reliably associated with the male gender and the duration of the disease longer than 60 months. An increased risk of POAG is noted in men with hypothyroidism averagely aged 69. In most cases, ophthalmic hypertension that accompanies endocrine pathology does not need any topical hypotensive treatment. The main pathogenetically validated therapy of thyroid disorders results in a reduction of IOP level and an improvement of fluid outflow from the eye.